2021
DOI: 10.7150/jca.53954
|View full text |Cite
|
Sign up to set email alerts
|

Hindsight: Review of Preclinical Disease Models for the Development of New Treatments for Uveal Melanoma

Abstract: The molecular, histopathological, genomic and transcriptomic characteristics of uveal melanoma (UM) have identified four molecular subgroups with different clinical outcomes. Despite the improvements in UM classification and biological pathology, current treatments do not reduce the occurrence of metastasis. The development of effective adjuvant and metastatic therapies for UM has been slow and extremely limited. Preclinical models that closely resemble the molecular and genetic UM subgroups are essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Corroborating the role of HO-1 in promoting UM progression, its selective inhibition, performed by VP13/47 supplementation at a final concentration of 50 μM, resulted in a reduction of cell proliferation ( Figure 2 A). VP13/47, designed by our research group, is a strongly selective HO-1 inhibitor (HO-1 IC 50 of 0.95 µM, HO-2 IC 50 > 100 µM) compared to other inhibitors reported so far [ 26 ]. Accordingly, the pharmacological effect of hemin on cell proliferation was abolished by concomitant treatment with VP13/47 ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…Corroborating the role of HO-1 in promoting UM progression, its selective inhibition, performed by VP13/47 supplementation at a final concentration of 50 μM, resulted in a reduction of cell proliferation ( Figure 2 A). VP13/47, designed by our research group, is a strongly selective HO-1 inhibitor (HO-1 IC 50 of 0.95 µM, HO-2 IC 50 > 100 µM) compared to other inhibitors reported so far [ 26 ]. Accordingly, the pharmacological effect of hemin on cell proliferation was abolished by concomitant treatment with VP13/47 ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…Efforts have been focused on investigating the underlying molecular and cellular processes that contribute to the development and metastasis of UM, to develop effective therapeutic approaches. To date, most in vitro studies exploring UM biology, development, progression, and metastasis, or searching for novel efficient treatments, are usually based on established UM cell lines [ 41 , 42 ], which remain essential tools during the preclinical investigation of disease pathogenesis and drug development [ 43 ]. To exemplify a few studies, Alvarez et al demonstrated the anti-cancer effect of mifepristone (MF), using both primary (92.1, MP41, MP46, MEL270) and metastatic (OMM2.5) UM cell lines.…”
Section: Current Status Of Rare Melanoma Experimental Modelsmentioning
confidence: 99%
“…Despite the considerable availability of UM in vitro models, a crucial aspect that needs to be considered when choosing the right model for preclinical studies is that some UM cell lines present genetic variations leading to an improper representation of the original tumor. For instance, UM presents a distinct genetic background compared to CM [ 41 ]; however, some cell lines derived from primary (OCM-1, OCM-3, OCM-8, SP6.5) or metastatic (MUM2C) UM were discovered to lack GNAQ and GNA11 mutations (found in 80% of UMs), while carrying BRAF (V600E) mutations, which are specific to CM [ 18 , 43 ].…”
Section: Current Status Of Rare Melanoma Experimental Modelsmentioning
confidence: 99%
“…The OMM2.5 cell line was derived from a liver metastasis and harbors the GNAQ mutation (c.626 A>C; p.Gln209Pro), BAP1 wild-type [25], and exhibits a mixed epithelioid and spindle morphology. We chose these two cell lines because they have different origins (primary uveal melanoma and uveal melanoma liver metastasis, respectively), both have been previously used in preclinical studies of targeted therapies [32], and they have different genetic backgrounds.…”
Section: Characterization Of Human Uveal Melanoma Cell Linesmentioning
confidence: 99%